Kematangan Sosial pada Remaja di Panti Asuhan Fahmi Makassar - Novita Ashari (LPPM Institut Pesantren KH. Abdul Chalim, 2021)
This study aims to see how the social maturity of adolescents at the Fahmi Orphanage Makassar. The research will use qualitative research methods. Qualitative research is the stage of the research approach and understanding that is sourced from the method of phenomena that occur in social life as well as problems between individuals. The subjects in this study were adolescents, both boys, and girls who were at the Fahmi Orphanage in Makassar. The results of this study are the social maturity of adolescents at the Fahmi Orphanage known by their family background. Adolescents who come from intact families have high self-confidence so that their social maturity is also good. Meanwhile, for adolescents who come from families who have low self-confidence so that their social maturity is not good.